Childhood, family and public policies: tensions and challenges - Zicavo Martínez, Nelson (2017)
A conceptual analysis of the relationships between childhood, family and public policies is made, considering the segregating tensions that operate as obstacles for qualitative and quantitative advances of transcendence; In particular with regard to the situation of children and adolescents. It is concluded that commitments are required to change and implement it based on efficient policies that implement and respect what is stated in conventions ratified as human rights.